2019
DOI: 10.1136/bmjopen-2018-028526
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation and exploration of telehealth in motor neuron disease in a UK specialist centre

Abstract: ObjectivesTo evaluate the processes involved in using a novel digitally enabled healthcare system (telehealth in motor neuron disease (TiM)) in people living with motor neuron disease (MND) and their informal carers. We examined TiM implementation, potential mechanisms of impact and contextual factors that might influence TiM implementation or impact.DesignAn 18-month, single-centre process evaluation within a randomised, pilot and feasibility study.InterventionTiM plus usual care versus usual care alone.Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 40 publications
2
46
0
1
Order By: Relevance
“…We also conducted a process evaluation of the TiM to understand how the system was used and to identify some of the potential impacts of the TiM on participants, carers and the MND service. This is reported in a parallel publication 29…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…We also conducted a process evaluation of the TiM to understand how the system was used and to identify some of the potential impacts of the TiM on participants, carers and the MND service. This is reported in a parallel publication 29…”
Section: Introductionsupporting
confidence: 55%
“…A detailed description of the TiM has been published 22. The use of the TiM in this trial is described in detail in the parallel publication describing the process evaluation 29. In brief patients and carers were asked to complete weekly sessions answering questions about their condition (such as functional ability, symptoms, depression and anxiety symptoms, carer strain) and patients recorded their weight and balance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was likely a result of the complexity of reporting and the high number of daily assessments in this study. In two other studies, good adherence with (bi-)weekly home-based selfmonitoring was observed (14,15). Accordingly, patients reported that technology was user-friendly and self-monitoring was easy (15,16).…”
Section: Low Burdenmentioning
confidence: 91%
“…So far, previous research on the use of telehealth in ALS has reported on home-based self-monitoring, videoconferencing, the store and forward method, and remote monitoring of noninvasive ventilation (17). A parallel publication reported on the use of a telehealth system similar to ALS Home-monitoring and Coaching, which also included a patient app for self-monitoring, a clinical portal, alerts and a telehealth nurse (15,18). In this trial, patients and caregivers reported that telehealth was easy to use, self-monitoring did not cost a lot of time and they would recommend telehealth to others.…”
Section: Low Burdenmentioning
confidence: 99%